Effect of POGIL Learning Model toward Students' Critical Thinking Skills on Buffer Solution Material - Fariza Anizarini; Endang Budiasih; Dedek Sukarianingsih (Universitas Negeri Malang, 2020)
One of the essential skills students should possess in the 2013 Curriculum is critical thinking. However, students' critical thinking skills in buffer solution material are considered low. Therefore, this study aims to identify the different critical thinking skills between students who attend a process-oriented guided oriented learning (POGIL) with and without science, environmental, technology, and society (SETS) approach on buffer solution material. This research uses quasi-experimental with a posttest-only control group design. The research results reveal that: (1) both POGIL learning models with and without the SETS approach are classified to be successfully carried out; (2) different critical thinking skills are found in students who learn using the POGIL learning model with and without the SETS approach on buffer solution material. The POGIL learning model with the SETS approach carries better students' critical skills results than the one with no SETS approach on the buffer solution material.